Morphometric Study about Effect of Sleep Deprivation on Prostate of Rats with Protective Effect of Omega 3 Fatty Acids - Nomana Mahmood, Kaukab Anjum, Uzma Shahid, Ayesha Shahid, Noreen Anwar, Madiha Ali, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Even though sleep makes up nearly a third of a person's lifetime, we do not fully appreciate its significance. The partial or nearly complete loss of sleep from an organism that results in a number of detrimental health issues is known as sleep deprivation. Aim: To investigate how omega 3 fatty acids affect the size and weight of the prostate gland in sleep-deprived rats. Study design: Random control trial. Methodology: Thirty male Sprague Dawley rats (population) aged three to four months and weighing 200 to 300 grammes were utilised. They were kept in a controlled setting at the NIH's animal house in Islamabad. Rats were randomised into three groups by using lottery method, with n = 10 rats in each group. The control group was designated as group A. They experienced a regular cycle of sleep and wakefulness. Rats in group B, which experienced sleep deprivation for 16 hours followed by an 8-hour sleep window each day for 8 weeks, were placed in the sleep-deprived group. The standard lab diet was provided to Groups A and B. For eight weeks, Group C received a typical lab meal combined with omega 3 fatty acids while also being sleep deprived for 16 hours, followed by an 8-hour sleep window each day. Results: In comparison to groups A and C that received omega 3, the gland weight and volume in group B were significantly lower. Group A: Weight and volume of the prostate: Prostate weight ranged from 1.85 to 0.50 grammes on average. The computed RTBWI was 0.60 + 0.22. The prostate's mean SD volume was 166.81 45.67 mm3. GROUP B: Weight of the prostate: Prostate weight ranged from 1.30 to 0.22 grammes on average. In the sleep-deprived group B compared to the control group A, the weight of the prostate was considerably lower (p-value=0.008). The computed RTBWI was 0.37 + 0.22. The prostate's mean SD volume was 127.88 67.35 mm3. GROUP C: Weight of prostate gland: In experimental group C, the prostate's mean SD weight was 2.19 0.42gm. According to the RTBWI calculation, it was 0.64 0.07. The prostate's mean SD volume was 182.89 44.16 mm3. Practical Implication: Today, sleep deprivation is a big problem, and this study will assist researchers in examining how Omega 3 fatty acids can help prevent this problem and the harmful effects it has on the prostate glands. Conclusion: It was concluded that Omega 3 fatty acids played a protective role while sleep deprivation had a negative impact on the weight and volume of the prostate gland. Keywords: Sleep Deprivation, Omega 3 Fatty Acids, Prostate and Protective Effect.